Social and ethnic disparities in stillbirth and infant death in Denmark, 2005–2016 - Trine Damsted Rasmussen (Nature Portfolio, 2021)
Abstract Ethnic disparity in stillbirth and infant death has been demonstrated in Europe. As the relation between migration and health change over time, this population based register study investigated the recent figures and explored if potential differences could be explained by the well-known educational and income inequalities in stillbirth and infant death using a novel approach. Stillbirth and infant mortality varied considerably according to country of origin, with only immigrants from China, Norway, and Poland having an overall lower risk than Danish women. Women of Pakistani, Turkish, and Somali origin had a particularly high risk of both outcomes. Women from recent high conflict areas displayed a pattern with increased stillbirth risk. An observed excess risks across generations was found, which is disturbing and rule out factors related to language barriers or newness. Differences in educational level and household income explained only part of the observed inequalities. Strengthening of the maternity care system to better understand and meet the needs of immigrant women seems needed to mitigate the disparities.